ANALYSIS OF DETERMINANTS OF COMPOSITE STOCK PRICE INDEX THROUGH STOCK TRANSACTION VOLUME ON THE INDONESIA STOCK EXCHANGE - Rahmad Zulhiansyah Simatupang; Isfenti Sadalia; Nisrul Irawati (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the influence of macroeconomic factors on the Composite Stock Price Index (IHSG) through the volume of stock transactions on the Indonesia Stock Exchange (IDX) during the period 2017–2023. The independent variables used in this study are the BI interest rate, the US dollar exchange rate, and inflation; transaction volume acts as an intervening variable, while the IHSG is the dependent variable. This study uses a quantitative method with a causal and explanatory approach. The analysis model used is the Error Correction Model (ECM) to identify short-term and long-term relationships between variables. The results of the study show that in the short term, inflation has a positive and significant effect on stock transaction volume, while the BI interest rate and exchange rate do not have a significant effect. In the long term, the BI interest rate and exchange rate have a significant effect on transaction volume. Meanwhile, on the IHSG, the BI interest rate and exchange rate have a significant effect in the long term, while transaction volume is only significant in the long term. The Sobel test shows that transaction volume significantly mediates the effect of the BI interest rate and exchange rate on the IHSG in the long term, but not in the short term. These findings underscore the importance of macroeconomic stability and market liquidity in influencing the performance of the Indonesian capital market. This study provides theoretical contributions to the development of literature on the role of macroeconomic variables in the capital market, as well as providing practical implications for investors, regulators, and issuers in formulating investment strategies and economic policies that support stock market growth.